High-salinity water as a cause of salt poisoning in livestock: two case studies in Northwestern Argentina = Agua con alta salinidad como causa de intoxicación por sal en ganado: dos estudios de caso del Noroeste de Argentina - Avellaneda Cáceres, Agustín; Medina, Diego Martín Nicolás; Aguirre Castro, Laura Sabrina; Sandoval, Gabriela Virginia; Singh Ruiz, Jeremias Dan; Micheloud, Juan Francisco (Facultad de Ciencias Veterinarias, Universidad Nacional del Nordeste, 2025)
This study aims to describe two outbreaks of salt poisoning in cattle and buffalo associated with the consumption of high-salinity water in northwestern Argentina. In both cases, elevated salinity in drinking water was associated with high mortality rates. In Santiago del Estero, calves that drank from an old well with high salinity experienced a mortality rate of 38%. Similarly, in San Pedro de Jujuy, buffalo and bulls exposed to saline water sources showed mortality rates of 10.8% and 13% mortality rates, respectively. Clinical signs included dehydration, diarrhea, and marked neurological symptoms such as ataxia and seizures. Postmortem examination revealed severe dehydration and mild brain lesions characterized by spongiosis and pseudolaminar necrosis, along with generalized vascular congestion and reactive changes in the capillary walls. Biochemical analyses confirmed elevated sodium concentrations in both serum and cerebrospinal fluid (CSF), supporting the diagnosis of salt intoxication. Water samples collected from the affected sites revealed total dissolved solids and salt concentrations significantly exceeding safe thresholds, underscoring the critical importance of water quality monitoring to prevent such toxic events in livestock.